HUKUM INTERNASIONAL SEBAGAI SALAH SATU JENIS HUKUM YANG PENTING ADANYA DALAM SUATU SISTEM HUKUM - Made Krishna Dwipayana Aryawan; Komang Febrinayanti Dantes; Si Ngurah Ardhya; Muhamad Jodi Setianto (Ganesha Law Review, 2022)
This study aimed to determine: (1) The definition of international law, (2) The history of international law, (3) The role of international law in resolving conflicts between countries. The data processing and analysis techniques in this article used a qualitative method with a literature review design. The results of the study indicated that International Law is one type of law that is important in its existence in a legal system. Therefore, we as students majoring in law, need to know the basics of this international law such as knowing the meaning, history and sources of law. In addition, international law is also useful for every country in the world, especially for countries that are experiencing conflict. This international law can be used to solve these problems so that peace between countries can be created.